Analysis of traffic accidents in Karachi, Pakistan - Lodi, Ashar Hashmat; Okuyama, Yasuhide; Morisugi, Hisa; Yordphol Tanaboriboon; Asian Institute of Technology Partial (Bangkok : Asian Institute of Technology, 1996)
Traffic accident is not simply a loss of one single life but it is an unrecoverable setback to all those concerned, furthermore, its a loss to the nation's economy. Being Transportation Engineers, ensuring safety should be the first priority. For this, all this research is about. The research mainly focuses on the traffic accident analysis for two of the busiest traffic corridors in Karachi, Pakistan. The prime purpose is to uncover the characteristics of the traffic accidents on the selected corridors in various ways and scenarios and to get line of action towards attainment of the traffic safety in the city. Furthermore, to develop a model for evaluation of a given road section as Hazardous or Safe, based on various traffic, geometric and road environment conditions by integrated use of cluster and discriminant analyses. The results from the analysis show 36% of the accidents involve pedestrians, while 55% of such accidents occur while pedestrians are crossing roads. The lack of pedestrian facilities is one of the prime reasons for such accidents. Although less number of females are involved in the accidents, but social setup of the country makes this population fraction more critical. In various types of intersections T-Type intersections are most critical, specially when operated under uncontrolled conditions. In some cases on corridor 2, signalized intersections are also critical, the reason is their counterfactual timings. The visibility, lane marking, lane width and traffic volume are the most sensitive parameters contributing towards traffic safety along the roads. On overall basis 25% of corridor I and 24% of corridor 2, are hazardous. The main conclusions of the study include recommendations for Traffic Engineering Bureau (TEB) to modify their accident reporting format. Furthermore, recommendations for road user safety are also discussed. The need of traffic safety awareness program is also stressed upon. This is necessary, so that the road users can recognize their rights and responsibilities in the traffic system. Since traffic volume has very high relation with accident rates, therefore recommendation is made to distribute traffic on the whole network of the city by adopting various Traffic Demand Management (TOM) Techniques. Furthermore, care should be given to maintain streets lighting and lane markings for better safety conditions.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1996
Keywords: Traffic accidents -- Pakistan -- Karachi